Working Still Harder. (March 2022) - Green, Francis; Felstead, Alan; Gallie, Duncan; Henseke, Golo
The authors use data from the British Skills and Employment Surveys to document and to try to account for sustained work intensification between 2001 and 2017. They estimate the determinants of work intensity, first using four waves of the pooled cross-section data, then using a constructed pseudo-panel of occupation–industry cells. The latter approach suggests biases in cross-section models of work intensity, associated with unobserved fixed effects in specific occupations and industries. The pseudo-panel analysis can account for slightly more than half (51%) of work intensification using variables that measure effort-biased technological change, effort-biased organizational change, the growing requirement for learning new things, and the rise of self-employment. The authors interpret the work intensification and these effects within a power-resources framework.